2019
DOI: 10.1111/ajt.15480
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcomes in de novo renal transplant recipients receiving everolimus-facilitated calcineurin inhibitor reduction regimen from the TRANSFORM study

Abstract: TRANSFORM (TRANSplant eFficacy and safety Outcomes with an eveRolimus‐based regiMen) was a 24‐month, prospective, open‐label trial in 2037 de novo renal transplant recipients randomized (1:1) within 24 hours of transplantation to receive everolimus (EVR) with reduced‐exposure calcineurin inhibitor (EVR + rCNI) or mycophenolate with standard‐exposure CNI. Consistent with previously reported 12‐month findings, noninferiority of the EVR + rCNI regimen for the primary endpoint of treated biopsy‐proven acute reject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
127
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 41 publications
(131 reference statements)
13
127
1
2
Order By: Relevance
“…Thus, in summary, this trial together with the results of other recent data provides further evidence, that MPA/tacrolimus remains current standard of care in de‐novo renal allograft recipients, despite all the well known‐limitations of this combination therapy. Everolimus is a well‐proven second‐line treatment option in case of MPA intolerability, such as severe viral infections, which are difficult to treat.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…Thus, in summary, this trial together with the results of other recent data provides further evidence, that MPA/tacrolimus remains current standard of care in de‐novo renal allograft recipients, despite all the well known‐limitations of this combination therapy. Everolimus is a well‐proven second‐line treatment option in case of MPA intolerability, such as severe viral infections, which are difficult to treat.…”
supporting
confidence: 55%
“…Because of reimbursement issues in Brazil for the expensive valganciclovir prophylaxis, drug‐related side effects, and only 6% CMV high‐risk patients, the Sao Paolo group explored the option of a preemptive CMV treatment strategy with tight CMV monitoring together with the use of mTOR inhibitors . The observation of lower CMV infection rates under mTOR inhibitors compared with MPA dates back from early clinical trials and was confirmed in recent trials and meta‐analyzes .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have indicated that a switch from CNI to EVR (withdraw CNI) showed more frequent DSA appearance and increased risk of ABMR than the standard regimen (with CNI) [21‐23]. Results of a recent comparative study between ‘EVR with reduced‐exposure CNI (EVR + rCNI)’ and ‘mycophenolate with standard‐exposure CNI’ have demonstrated lowered incidence of de novo DSA and similar cellular rejection rate in the EVR + rCNI arm among on‐treatment patients [24]. Although EVR might have the potential to reduce DSA‐induced humoral rejection, we need to carefully assess the efficacy of EVR considering combined use of CNI.…”
Section: Discussionmentioning
confidence: 99%